Pengembangan database Management system menggunakan My SQL - Siregar, Ummi Kalsum; Sitakar, Tutur Arbaim; Haramain, Sultan; Lubis, Zaidah Nur Salamah; Nadhirah, Ulfi; Yahfizham, Yahfizham (Lembaga Riset Mutiara Akbar, 2024)
In today's digital era, the development of Database Management Systems (DBMS) explores the important role of storing, managing and accessing data efficiently. This research aims to analyze the DBMS development process using MySQL. Initial planning, where business needs and data requirements are identified. The database structure is then designed by considering normalization and relationships between entities. After installing MySQL, a database is created with a predetermined design. Next, the table is implemented by setting the columns, data types, and primary/foreign keys. User access rights are defined to ensure data security, and functions and stored procedures are implemented to facilitate complex data processing. Indexes are added to improve query performance. Backup and recovery management is an important focus in ensuring data continuity. Application integration is carried out by matching the application interface with the database system using the MySQL API or driver. This research presents a systematic guide for DBMS development using MySQL. Overall, using MySQL as a database management system offers flexibility, high performance and reliable security to support business needs in storing and managing data.